The danger of human alienation in the conditions of technical civilization - Koka Kutubidze; Maia Gelashvili (Reviews of Modern Science, 2025)
The presented article analyzes scientific-technological progress and reveals that the process of civilization and globalization has both positive and negative tendencies according to sociology. Before our era, there has never been so evidently revealed conflict between human beings and the technological environment of nowadays. A human being wasn’t vulnerable to unpredictable processes currently occurring in the field of Technology. In the condition of technological progress, the special relationship aspects between human beings and technology and their capabilities weren’t always taken into consideration. The nature and nuances of technological processes should always serve and meet the demands, goals, and objectives of society. Technology is in control of the person and not Vice versa -a person is in control of technology, and in such case, this situation becomes dangerous for mankind and for their existence.